Polityka socjalna i redystrybucja przychodów między harmonizacją a konkurencją w rozszerzonej Unii Europejskiej - Apolte, Thomas (Social Policy and Income Redistribution between Harmonization and Competition in an Enlarged European Union, 2005)
The enlargement of the European Union will clearly deepen regional income disparities across the member states of the EU. From the point of view of the economics of integration, no serious problems are to be expected. On the contrary, integration of goods and service markets as well as factor markets will improve the welfare level of both rich and poor countries alike. If any welfare losses are to be expected; then these losses will be rooted in trade-division effects resulting from the integration of the new members into the customs union of the EU but not from different levels of productivity and income. By contrast, no such a clear cut statement can be derived when the different system of welfare and income redistribution in the old and new member countries are considered. The reason is that movements of factors of production due to differences in productivity increase overall welfare, whereas movements induced by redistributive policies distort regional factor allocation. Moreover, movements of factors and persons may, under certain circumstances, discourage redistributive policies and, hence, result in inefficient levels of income redistributive. Finally, differences in social policy and income redistributive may hamper factor-market integration. A migration of employee hand accumulated prior to migration. Nevertheless, it would simplify things far to much just to call for a centralization of redistributive policy in the European Union. First of all, decentralized redistributive policies have their own merits since they can take regional preferences into account. And secondly, in order to see whether these issues are more than just theoretical eventualities of a mere academic relevance it has first to be clarified how real-world social policy systems in Europe are constructed and how they interact. In this contribution. I will firstly give a brief overview of the most prominent theoretical aspects of decentralized income redistribution in a number of economically integrated countries like the European Union. I will then show, how the most important systems of social policy in the European Union interact and how they may be affected by the integration of central and eastern European countries (CEEC).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1056, s. 94-106